Livestock Disease and Health Care Facility in Sundarbans Delta of India - Das, Samares Kumar; Tripathi, Hema (Indian Journal of Extension Education, 2013)
There are a number of livestock diseases which are seasonal in nature. Understanding the disease pattern and health care  facility has an implication in formulating an efficient and effective disease management strategy. With this implication, a  study was conducted in four villages of Sundarban delta of India to understand the prevalence of livestock disease, their  seasonality, and health care facility available. A participatory case study method was used for the study. Data were  collected using semi-structured interview, listing, narrative and observation method. Study reveals that foot and mouth  disease, ranikhet disease, chicken pox, hump sore, etc. were highly seasonal, whereas amphistomiasis, delayed expulsion  of placenta, dystokia, etc. were not seasonal. Quacks, veterinary officers, medicine pedlars, medicine shop keepers, mid wives, and ethno-veterinarians were the veterinary service providers in the study area. It is concluded that a holistic  research is needed on documentation and validation of major livestock diseases in order to suggest effective disease  management practices in the context of prevailing health care practices and available veterinary facilities.
Keywords: Livestock disease; seasonality; sundarban delta; health care facility